PERANCANGAN SISTEM INFORMASI HUMAN RESOURCE DEVELOPMENT BERBASIS WEB MENGGUNAKAN FRAMEWORK ODOO DI PT. NURO INTELIA PROSPERA JAKARTA - Cahyadi Agustin (POLITEKNIK PIKSI GANESHA, 2021)
This study aims to analyze, design and build the implementation of the Human Resource Development information system at PT. NURO INTELIA PROSPERA JAKARTA. The research method used is descriptive qualitative method. The data collection technique used is literature study, field study. The method used in system development is waterfall. From the research conducted, it was found that there are problems in the management of Human Resource Development. The integration data management process is still not global, so it is still not effective in terms of data input procedures, data storage, data retrieval and report generation. Therefore, a Human Resource Development information system was created using the Python programming language and PostgreSQL as a database.The suggestions given to deal with existing problems include: 1) Optimizing the Human Resource Development system using a system that has been designed, 2) Developing and updating the system to improve the quality of the system so that it can be used further.